ENHANCING THE CUSTOMER EXPERIENCE WITH CRM SYSTEMS: A CASE STUDY OF THE HOTEL INDUSTRY - Gulomkodirova Mamura (University Research Base, 2024)
In the highly competitive hotel industry, delivering a superior customer experience is essential for success. Research shows that even a 1% increase in customer satisfaction can lead to a 5% increase in revenue. The hotel industry is increasingly reliant on CRM systems to improve the customer experience and boost revenue. However, there are challenges associated with implementing and using these systems effectively. This study will explore the impact of CRM systems on the customer experience in the hotel industry. The study will examine how CRM systems are currently used in the industry, the challenges that hotels face in implementing them, and the strategies they use to overcome these challenges. It will also explore the potential benefits of using CRM systems. It is hoped that the findings of this study will provide valuable insights into the use of CRM systems in the hotel industry and how they can be used to improve the customer experience. The study will also provide recommendations for hotels on how to effectively implement and use CRM systems to achieve their business goals.